1997
DOI: 10.1016/s0896-6273(00)80264-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Dominant Negative FGF Receptor Inhibits Axonal Growth and FGF Receptor Phosphorylation Stimulated by CAMs

Abstract: The cell adhesion molecules (CAMs) NCAM, N-cadherin, and L1 are homophilic binding molecules that stimulate axonal growth. We have postulated that the above CAMs can stimulate this response by activating the fibroblast growth factor receptor (FGFR) in neurons. In the present study, we demonstrate that activation of NCAM and L1 can lead to phosphorylation of the FGFR. Both this and the neurite outgrowth response stimulated by all three of the above CAMs are lost when a kinase-deleted, dominant negative form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
243
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(256 citation statements)
references
References 52 publications
(37 reference statements)
10
243
3
Order By: Relevance
“…For example, differential signaling between NCAM and c-Ret may regulate the balance between stem cell self-renewal and differentiation. Interestingly, it has been reported that NCAM-mediated cell-cell adhesion leads to activation of FGF-receptor tyrosine kinase, which is required for NCAM-induced neurogenesis (27). These studies indicate cross-talk occurs between NCAM binding and the FGF signaling pathway.…”
Section: Discussionmentioning
confidence: 93%
“…For example, differential signaling between NCAM and c-Ret may regulate the balance between stem cell self-renewal and differentiation. Interestingly, it has been reported that NCAM-mediated cell-cell adhesion leads to activation of FGF-receptor tyrosine kinase, which is required for NCAM-induced neurogenesis (27). These studies indicate cross-talk occurs between NCAM binding and the FGF signaling pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, basic studies have shown the presence of the interactions between N-cadherin and fibroblast growth factor (FGF) receptor (Doherty and Walsh, 1996;Saffell et al, 1997). Hazan et al (2000) demonstrated that treatment with FGF-2 induced N-cadherin-expressing breast carcinoma cells into a more invasive phenotype, with upregulation of matrix metalloproteinase MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM has been demonstrated to induce neurite outgrowth by activation of the Ras-MAP kinase cascade and a pathway involving the fibroblast growth factor receptor, PLC␥ and PKC (Williams et al, 1994;Saffell et al, 1997;Schmid et al, 1999;Kolkova et al, 2000). To clarify whether cytNCAM-140 is involved in NCAM-dependent activation of the Ras-MAP kinase pathway, constitutively active MEK2 was expressed in PC12-E2 cells transfected with cytNCAM-140.…”
Section: Discussionmentioning
confidence: 99%